2020
DOI: 10.1155/2020/8876565
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Differential Intestinal Mucosa Transcriptomic Biomarkers for Ulcerative Colitis by Bioinformatics Analysis

Abstract: Background. Ulcerative colitis (UC) is a complicated disease caused by the interaction between genetic and environmental factors that affect mucosal homeostasis and triggers inappropriate immune response. The purpose of the study was to identify significant biomarkers with potential therapeutic targets and the underlying mechanisms. Methods. The gene expression profiles of GSE48958, GSE73661, and GSE59071 are from the GEO database. Differentially expressed genes (DEGs) were screened by the GEO2R tool. Next, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 54 publications
(49 reference statements)
0
8
0
Order By: Relevance
“…However, differences in measurement platforms, lab protocols, sample sizes, and operators render gene expression levels incomparable. In recent years, several studies based on microarray technology have been published to identify effective biomarkers in UC, most of which are prone to utilizing intersecting genes from different microarrays to perform analyses (Cheng et al, 2019(Cheng et al, , 2020Shi et al, 2020;Cao et al, 2021). As shown in Table 3, these methods can be applied to fewer datasets (≤3 datasets) because more datasets represent overly strict inclusion criteria, leading to fewer DEGs.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, differences in measurement platforms, lab protocols, sample sizes, and operators render gene expression levels incomparable. In recent years, several studies based on microarray technology have been published to identify effective biomarkers in UC, most of which are prone to utilizing intersecting genes from different microarrays to perform analyses (Cheng et al, 2019(Cheng et al, , 2020Shi et al, 2020;Cao et al, 2021). As shown in Table 3, these methods can be applied to fewer datasets (≤3 datasets) because more datasets represent overly strict inclusion criteria, leading to fewer DEGs.…”
Section: Discussionmentioning
confidence: 99%
“…The expression of the six hub genes was confirmed in the DSS-induced UC mouse model. In published studies, some scholars screened diagnostic biomarkers for UC from the DEGs identified from a single dataset or an overlap of two or three datasets via bioinformatics analyses (Cheng et al, 2019(Cheng et al, , 2020Shi et al, 2020;Cao et al, 2021). In contrast, the advantage of this research lies in the larger dataset obtained by combining data from six GEO datasets, which increased the sample size and ensured the stability and relative reliability of the conclusions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Transcriptomics is a high-throughput technique to observe mRNAs with differential expression in different tissues and time points in organisms, playing a major role in the study of drug action mechanism [ 39 , 40 ]. In this study, 370 differentially expressed genes, including 151 upregulated and 219 downregulated, were screened.…”
Section: Discussionmentioning
confidence: 99%
“…The National Center for Biotechnology Information Gene Expression Omnibus ( ) is a free public database of microarray/gene profiles, which was used to obtain the GSE59071 ( 19 ) and GSE107597 ( 20 ) in UC and normal tissue gene expression profiles ( 21 ). GEO2R (ncbi.nlm.nih.gov/geo/geo2r/) was used for data preprocessing and analyzing the expression of TRIM22 in the UC (n=6) and control (n=6) groups (GSE59071: 97 UC and 11 control samples; GSE107597: 6 UC samples and 4 control samples).…”
Section: Methodsmentioning
confidence: 99%